2012
DOI: 10.1037/a0028773
|View full text |Cite
|
Sign up to set email alerts
|

A case study of sexual abuse and psychological correlates among an HIV-serodiscordant couple.

Abstract: Childhood sexual abuse (CSA), adult sexual abuse (ASA) and intimate partner violence (IVP) are documented risk factors for HIV infection and are often implicated in the presentation of mental health disorders in both males and females, including those who are vulnerable to HIV-infection (African-Americans; trauma survivors). As such, these issues may contribute to health-related challenges among couples, particularly if the individuals are impacted by histories of trauma and HIV. Presented here is a case study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Previous intervention studies on serodiscordant couples have demonstrated a decrease in HIV transmission protective behaviours in couples where one or both partners had clinically significant symptoms of PTSD. [25] These findings suggest that the success of sexual risk reduction interventions may be attenuated and compromised by the presence of physical or sexual trauma histories and residual mental health issues, such as PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous intervention studies on serodiscordant couples have demonstrated a decrease in HIV transmission protective behaviours in couples where one or both partners had clinically significant symptoms of PTSD. [25] These findings suggest that the success of sexual risk reduction interventions may be attenuated and compromised by the presence of physical or sexual trauma histories and residual mental health issues, such as PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual Education ‐ Helping families understand the importance of parental involvement and shared decision‐making in relationships for sexual risk reduction in young women (Kogan, Simons, Chen, Burwell, & Brody, ). ‐ The success of sexual risk reduction interventions may be attenuated by sexual traumas histories and comorbid mental health issues. (Wyatt, Loeb, Williams, Zhang, & Davis, ). ‐ Promoting condom use and mutual masturbation as a safe sex practice was effective in increasing condom use in Peurto Rico (Pérez‐Jiménez, Seal, & Ronis, ). …”
Section: Resultsmentioning
confidence: 99%
“…-The success of sexual risk reduction interventions may be attenuated by sexual traumas histories and comorbid mental health issues. (Wyatt, Loeb, Williams, Zhang, & Davis, 2012).…”
Section: Sexual Educationmentioning
confidence: 99%
“…The seronegative partner, although not physically affected by HIV, also bears devastating psychological burdens such as fear of transmission, stress associated with caretaking, anger associated with betrayal (if their partner acquired HIV through extra-relational sex), and concern about the partner’s deteriorating health as well as anticipated loss (Beyeza-Kashesya et al, 2009; Gordon-Garofalo & Rubin, 2004; Rispel, Cloete, Metcalf, Moody, & Caswell, 2012). The mental health challenges may compromise treatment adherence, may heighten HIV transmission risk for couples affected by HIV/AIDS (Bradley, Remien, & Dolezal, 2008; Wyatt, Loeb, Williams, Davis, & Zhang, 2012), and warrant further investigation with different types of couples.…”
mentioning
confidence: 99%